2020
DOI: 10.1186/s12886-020-01354-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy with or without internal limiting membrane peeling for myopic foveoschisis

Abstract: Background: The aim of this study was to compare the anatomical and visual outcomes of vitrectomy with or without internal limiting membrane (ILM) peeling for symptomatic myopic foveoschisis (MF). Methods: A retrospective cohort study of patients who had undergone vitrectomy for symptomatic MF at our specialist ophthalmology department in China. Cases were retrospectively categorized into one of two cohorts, depending on whether or not they had undergone ILM peeling (ILMP) during their surgery. Over a mean fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A total of 645 articles were identified through database searching. After excluding 98 duplicates and 223 studies such as systematic reviews and case reports, 10 articles [ 9 18 ] were ultimately included for meta-analysis based on the inclusion and exclusion criteria and after full-text assessment for studies with unclear diagnostic criteria and non-conforming interventions. The literature selection flowchart is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 645 articles were identified through database searching. After excluding 98 duplicates and 223 studies such as systematic reviews and case reports, 10 articles [ 9 18 ] were ultimately included for meta-analysis based on the inclusion and exclusion criteria and after full-text assessment for studies with unclear diagnostic criteria and non-conforming interventions. The literature selection flowchart is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many vitreoretinal surgery modalities have been reported, and a combination of pars plana vitrectomy, internal limiting membrane peeling, with or without macular buckle, is generally believed to achieve a good visual outcome by eliminating both tangential and anterior–posterior tractions ( 12 ). Vitrectomy alone without inner limiting membrane peeling, but with careful removal of the posterior hyaloid, has also been shown to produce a comparable outcome compared with vitrectomy with inner limiting membrane peeling ( 13 ). Zhao et al ( 14 ) demonstrated favorable long-term results of macular buckling for highly myopic eyes with both myopic foveoschisis and macular holes.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, after PSR followed by vitrectomy, OCT showed that 95.45% of MF eyes achieved complete resolution of the MF, and the remaining 4.55% of MF eyes achieved partial resolution. While only 61.0%-80.0% of eyes achieved total resolution of foveoschisis after PPV alone [17,[20][21] , and only 83.33% of eyes achieved complete resolution of foveoschisis after PSR alone [18] . Our current study showed that PSR followed by vitrectomy got better BCVA improvement and MF resolution than that of PSR or vitrectomy alone.…”
Section: Discussionmentioning
confidence: 99%